Performances of cascade control with variations of process parameters and tuning methods [electronic resource] - Tee, Shin Yee, 1990-, author; Kamarul Asri Ibrahim, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2013